Upward Mobility and the Common Good : Toward a Literary History of the Welfare State - Robbins, Bruce (Book collections on Project MUSE., 2007)
We think we know what upward mobility stories are about--virtuous striving justly rewarded, or unprincipled social climbing regrettably unpunished. Either way, these stories seem obviously concerned with the self-making of self-reliant individuals rather than with any collective interest. In Upward Mobility and the Common Good, Bruce Robbins completely overturns these assumptions to expose a hidden tradition of erotic social interdependence at the heart of the literary canon. Reinterpreting novels by figures such as Balzac, Stendhal, Charlotte Bronte, Dickens, Dreiser, Wells, Doctorow, and Ish.